Success on your certificate course in English language teaching : a guide to becoming a teacher in ELT/TESOL / Caroline Brandt. - Brandt, Caroline (SAGE Publications, 2006)
"Extremely comprehensive and well written in terms of style accessible to the reader, but intelligent and expressing some fairly subtle concepts. Would that more ELT practitioners could do the same!. Certainly a good read for those thinking about and also those engaged in initial training or even post initial training stage"--Jenny Pugsley, Head of TESOL, Trinity College London. Each year, thousands of people all over the world take one of the hundreds of available short pre-service courses that lead to the award of a certificate in English Language Teaching (ELT) or Teaching English to Spea.